Ruang Terbuka Hijau (RTH) Maron Genteng Banyuwangi dan Pandangan Aspek Keagamaan - Mahfud, Ali (MOMENTUM : Jurnal Sosial dan Keagamaan, 2019)
The metamorphosis of public organizations in response to internal and external demands is manifested in the form of reform, revitalization and the formation of government networks. The government is required to always adjust to the development of the environment. This adjustment is an effort to respond to the development of society and the global environment. External factors require public organizations to be more flexible in governance. This article wants to discuss the efforts of the Banyuwangi Regency government and the collaboration that was carried out in order to fix green open space in Banyuwangi Regency, East Java. The approach used in writing this paper is a socio-legal approach that combines normative approaches with research results, assessment results, and other references and is reinforced by empirical research conducted through interviews andobservations. This research found the existence of efforts by the city government to develop regulations related to the regulation of green open space as well as various collaborative efforts between government, civil society and the private sector in the implementation of the development of green open spaces in Banyuwangi Regency. The preparation of legal instruments and the establishment of government networks is actually part of the new public governance paradigm that seeks to optimize the roles of government and stake holders in the development of green open spaces. This study also found that the role of the community as a civil society was considered important in promoting democratic governance, the effectiveness of regulations that were oriented to the public interest